The Effect of the Traditional Sack Race Game on the Lower Limb Muscle Strength of Fifth-Grade Elementary School Students - Acep Abdul Aziz; Yopa Taufik Saleh; Rahmat Permana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to examine the impact of physical activity based on local wisdom, specifically through the traditional sack race, on lower-limb muscle strength in Physical Education, Sports, and Health (PJOK) classes for fifth-grade elementary school students. The intervention was designed in a structured manner, following the principle of progressive overload, and implemented over six sessions. A quantitative approach using a True Experimental Design via a Pretest-Posttest Control Group Design was applied in this study. The entire population of 28 fifth-grade students at SDN Cicariu was included as participants using total sampling, who were then randomly assigned to an experimental group (n = 14) and a control group (n = 14). The experimental group received a learning program based on the traditional sack race game, while the control group followed conventional Physical Education (PJOK) instruction. Data on lower-body muscle strength were collected via the vertical jump test, which was subsequently analyzed using descriptive statistics and the non-parametric Mann–Whitney U test at a significance level of 0.05. The research results showed an upward trend in the average scores for both groups; however, the experimental group recorded a significantly higher percentage increase of 16.66% compared to the control group, which increased by only 5.36%. Through the Mann–Whitney U test, an Asymp. Sig. A value of 0.089 (p > 0.05) was obtained. This study concludes that physical activity through sack races is descriptively effective in stimulating lower limb muscle strength in elementary school-aged children. Implicitly, traditional games packaged systematically can be adopted by physical education teachers as a recreational yet educational alternative for physical activity to optimize students’ physical capacity without relying on expensive facilities.